Relationship of personality factors and purchase intention of counterfeit products among college students - Leong, Mei Kei; Osman, Syuhaily; Abu Bakar, Nur Syaheera (Malaysian Consumer and Family Economics Association, 2017)
This study aims to determine the influence of personality factors which inclusive of price consciousness, fashion consciousness and value consciousness towards purchase intention of counterfeit products among college students. A total of 178 respondents have been selected through two levels of sampling, which are simple random sampling and systematic random sampling. Pearson correlation analysis showed that there were significant relationships between price consciousness towards purchase intention of counterfeits products (r=0.394, p=0.000) and fashion consciousness towards purchase intention of counterfeits products (r=0.475, p= 0.000). The result of multiple Regression showed that fashion consciousness is the main influence on purchase intention (β= 0.386, p<0.001). Based on the result, it gives the implication of knowledge to the consumers to further understand consumers' behaviour. Besides that, it also enables the producer of the original products to propose suitable designs and pricing structure to attract price consciousness and fashion consciousness consumers in purchasing original goods.